Estudo teórico da estabilidade lateral de hastes submetidas a uma protensão externa - Tavares, Gil Augusto (1977)
The lateral stability of beams submitted to an external "protension" is investigated by applying the "Dynamic Criteria of Stability", via the Rayleigh-Ritz Method. An analysis of bifurcation taking into account the non-linear terms, for one of the considered cases is made, as well as a discussion on stability by means of the parameters of the characteristic equation obtained from the eigenvalue problem.